PROGRAM PENINGKATAN DAN PELATIHAN KURIKULUM TEKNOLOGI KOMPUTER JARINGAN TINGKAT SMK TERPADU YAYASAN GEMA CENDEKIA MUSLIM LOMBOK TENGAH - Made Sutha Yadnya; Djulfikri Budiman; Cipta Ramadhani; Bulkis Kanata; Paniran Sudi Mariyanto Al Sasongko (Universitas Mataram, 2022)
Background: Users or recipients of SMK graduates are focused on the field of Network and Computer Engineering providing input so that graduates are ready to use. Training to improve the quality of graduates really needs to be held in a community service program. The training was carried out at the Integrated Vocational School of the Gema Cendikiawan Muslim Foundation (YGCM) in Central Lombok, which is very closely related to improving the learning curriculum in the field of Computer and Network Engineering. This increase is related to the very rapid development of technology accompanied by the need for uptake of graduates who can work according to the abilities obtained at the SMK bench. Purpose: The activities carried out are to motivate enthusiasm to be raised by teaching and learning process activities for teachers and students given an overview of current conditions and the future, so that future technology is still used according to the basic competencies given to students by improving the curriculum according to market share needs. Method: Motivation is carried out before designing the curriculum so that in the process of determining curriculum outcomes, minimum requirements are obtained to suit users of SMK graduates, discussions with surfing the internet continue to be carried out as an effort to produce graduates as optimally as possible. Results: Teachers and students are very enthusiastic about participating in the program, it was found one important thing in this program is the importance of knowledge of healthy Internet use, especially IoT in the future, the curriculum obtained from this activity adopts market demand of around 76% Conclusion: This training should continue to be implemented so that the curriculum continues to be updated according to the needs of the market share.